THE USE OF HORROR STORY IN IMPROVING STUDENTS’ READING COMPREHENSION FOR ELEVENTH GRADE OF SMAN 3 SINJAI - Basri, Muthaharah; Mardianah, Mardianah; T, M. Rusdi (English Language Teaching for EFL Learners Journal, 2020)
This research aimed at investigating how the horror story was use in the reading class to improve the students’ reading comprehension of the eleventh grade at SMAN 3 Sinjai. The variables of this research were Horror Story as an independent variable and Reading Comprehension as a dependent variable. The method used in this research was Quasi Experimental research. There were two classes used as the subject in this research; MIA 3 as experimental class and MIA 2 as controlled class. The total population of this research was 186 students taken from the eleventh-grade students of SMAN 3 Sinjai. The total sample of this research was 40 students. The sample was chosen purposively. The instrument of this research was an essay test which was given both in pre-test and post-test. The result of the research shows that the students’ performance in pre-test was better compared to that in post-test. In experimental class, the mean score of pre-test was 74.9 (good) and the mean score of post-test was 87.7 (excellent). While in controlled class, the mean score of pre-test was 68.55 (fair) and the mean score of post-test was 77.85 (good). While both of the classes are improved, the significant improvement was occurred in experimental class from fair to very good score. Besides, in controlled class the improvement was only from fair to good score. In addition, the t-test value (2.23) was higher than t-table value (2.024). Based on the findings, the researcher concluded that the implementation of Horror Story was effective to enhance the students’ reading comprehension in the eleventh-year students of SMAN 3 Sinjai in academic year 2018/2019. This story makes the students learn with fun and directly involve in classroom activities.